Contribution of immunoglobulin products in influencing seasonal influenza infection and severity in antibody immune deficiency patients receiving immunoglobulin replacement therapy - Ballow, Mark; Ortiz-de-Lejarazu, Raúl; Quinti, Isabella; Miller, Matthew S.; Warnatz, Klaus (Frontiers in Immunology, 2024)
Seasonal and pandemic influenza infection present a potential threat to patients with antibody deficiency. The acceptance and effect of the current recommendation for annual vaccination against influenza for patients with antibody deficiency is not well investigated and due to antigenic drift or shift the protective capacity of regular IgG replacement therapy (IgRT) is considered low. This narrative review considers the effect of influenza vaccination in immunodeficient patients and discusses available information on the effect of immunoglobulin products on seasonal influenza infectivity and severity in antibody deficiency patients receiving IgRT. The humoral immune response to seasonal influenza vaccination is reduced in patients with antibody immune deficiency. However, there is no evidence that the proportion of patients with primary antibody deficiency who develop influenza illness, and the severity of such illness, is increased when compared with the general population. The IgRT that patients receive has been shown to contain neutralizing antibodies as a consequence of past flu infections against both the hemagglutinin and neuraminidase surface proteins and other viral internal proteins of different influenza A virus strains. Studies have demonstrated not only significant levels of specific but also cross-reactive antibodies against seasonal influenza virus strains. Thus, despite the yearly changes in influenza viral antigenicity that occur, IgRT could potentially contribute to the protection of patients against seasonal influenza. Currently, only limited clinical data are available confirming a preventative effect of IgRT with respect to seasonal influenza infection.In conclusion, there is some evidence that IgRT could contribute to protection against seasonal influenza in patients with antibody-related immunodeficiency. However, additional clinical data are needed to confirm the extent and relevance of this protection and identify the main responsible virus targets of that protection.